Analysis of Current Rules and Regulations for Preclinical Studies of Radiopharmaceuticals - A. S. Lunev; K. A. Petrosova; K. E. Ternovskaya; A. D. Sklyarenko; A. E. Surnina; А. I. Nigmatulina (Регуляторные исследования и экспертиза лекарственных средств, 2024)
SCIENTIFIC RELEVANCE. Owing to specific aspects of their development and use, radiopharmaceuticals require separate rules and regulations for preclinical studies. However, current legislation and regulations on the organisation and conduct of preclinical studies of radiopharmaceuticals contain a number of contradictions and need improvement.AIM. This review aimed to analyse the rules and regulations governing preclinical studies of radiopharmaceuticals in the Russian Federation and abroad.DISCUSSION. The regulatory requirements for preclinical studies of radiopharmaceuticals that are conducted by specialised institutions in Russia and abroad have several shortcomings and inconsistencies. Laboratories working with animals and open sources of ionising radiation should prioritise regulations related to radiation safety. Radiation safety requirements should be in line with the sanitary standards and practical guidelines used in preclinical studies. This review covers the specific aspects of conducting preclinical studies of therapeutic and diagnostic radiopharmaceuticals. According to the review results, international guidelines for preclinical studies of radiopharmaceuticals focus on systematising the applicable requirements and aim at providing a consistent approach to preclinical studies to reduce the conduct of studies that are not informative for a specific radiopharmaceutical product.CONCLUSIONS. Radiation safety requirements should be harmonised with international guidelines. Methodological recommendations and local regulations should be developed and approved to facilitate the resolution of regulatory issues related to the organisation and conduct of preclinical studies of radiopharmaceuticals. Many medical, social, technical, and administrative issues need addressing at the inter-institutional and/or national level.